Mythology Unbound An Online Textbook for Classical Mythology - Mellenthin, Jessica; Shapiro, Susan O.; Open Textbook Library (Open Textbook Library, 2017)
Mythology Unbound
Aegis -- Agamemnon and Iphigenia -- Aphrodite -- Apollo -- Ares -- The Argonauts -- Artemis -- Athena -- Caduceus -- Centaurs -- Chthonian Deities -- The Delphic Oracle -- Demeter -- Dionysus/Bacchus -- Hades -- Hephaestus -- Hera -- Heracles -- Hermes -- Hestia -- Historical Myths -- The Iliad - An Introduction -- Jason -- Miasma -- The Minotaur -- The Odyssey - An Introduction -- The Oresteia - An Introduction -- Origins -- Orpheus -- Persephone -- Perseus -- Poseidon -- Prometheus -- Psychological Myths -- Sphinx -- Story Pattern of the Greek Hero -- Theseus -- The Three Types of Myth -- The Twelve Labors of Heracles -- What is a myth? -- Why are there so many versions of Greek myths? -- XeniaZeus
In English.
Description based on print resource
Keywords: History -- Textbooks